1999
DOI: 10.1111/j.1365-2141.1999.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of primitive peripheral blood cells: synergism of interleukin 12 with interleukin 6 and stem cell factor

Abstract: Interleukin-12 (IL-12), a heterodimeric cytokine with potent biological activity, was evaluated for effects on proliferation of human immature progenitor cells in vitro. In vitro proliferation of 5-FU-resistant CD34+ (G0) peripheral blood stem cells (PBSC) in response to sequential cytokine stimulation was examined in the presence and absence of 100 ng/ml IL-12. PBSC were found to include a subpopulation of cells that were resistant to 25 microg/ml 5-FU and required a combination of IL-12, IL-6 and SCF for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Similarly to another study [24], HSCs constitutively produced sIL‐6R at a basal level (54.8 ± 6.5 pg/ml per 1.5 × 10 5 CD133 + untreated cells for a period of 24 hours) (Fig. 2).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Similarly to another study [24], HSCs constitutively produced sIL‐6R at a basal level (54.8 ± 6.5 pg/ml per 1.5 × 10 5 CD133 + untreated cells for a period of 24 hours) (Fig. 2).…”
Section: Resultssupporting
confidence: 68%
“…We opted for a preculture with 5‐FU, which is an antimetabolite that inhibits thymidine synthase and kills all cycling cells. This method has been previously used to select quiescent or slow‐dividing hematopoietic stem/progenitors cells [24, 36–38], which are considered the most primitive cells [35, 3941]. Cell‐cycle analyses showed that, after 5‐FU pretreatment in the presence of IL‐3, part of the G 0 CD133 + population was recruited and entered apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation